Comparison of the Optical Amplifiers EDFA and SOA Based on the BER and Q-Factor in C-Band. (9th January 2017) - Ivaniga, Tomáš; Ivaniga, Petr
Abstract : Currently it is not possible to create a fully optical communication system without a software tool which simulates an optical communication line in real conditions prior to its construction. The aim of this article is to establish a comparison between the EDFA (erbium doped fibre amplifier) and SOA (semiconductor optical amplifier) optical amplifiers in the WDM (wavelength division multiplexing) system. The system contains a four-channel WDM with speed of 10 Gbps and optical fibre with length of 80 km. Simulations are conducted in the programme environment " OptSim ." The quality of the optical communication system is evaluated by the BER (bit error rate) andQ -factor for individual wavelengths, namely, of 1558 nm and 1562 nm, which are within the C-band.